Real exchange rates and target interest rates in a simple VAR model - Mollick, André Varella (2018)
This paper proposes a simple vector autoregressions (VAR) model with (real) output and exchange rate shocks on interest rates. Rather than assuming non- recursive identification schemes, we test the identifying assumption of the error term decompositions. Applying the model to quarterly data on major currencies against the U.S. dollar (USD) from 1974 to 1997, interest rate shocks explain – after 3 years – 16% of Canadian dollar/USD (CAD) real exchange rate variations and less than 2% for the mark/USD and yen/USD. Positive innovations of interest rates bring about (transitory) CAD real appreciations in differences and (permanent) appreciations in levels. Canadian real output is more explained by domestic interest rate shocks (19%) than Germany’s (5%) or Japan’s (0.2%). Canada is smaller than the other economies and CAD has been shown to suffer from “fear of floating”. Our findings support the proposition that domestic shocks dominate output variance under fixed exchange rates. They are also consistent with structural interpretations of the VAR.